The role of domestic violence in pregnancy on maternal and fetal outcomes, a narrative review in past decade of studies in Iran. - Dolatian, Mahrokh; Mirabzadeh, Arash; Setareh Forouzan, Ameneh; Sajjadi, Homeira; Alavi Majd, Hamid; Moafi, Farnoosh (Advances in Nursing & Midwifery, 2013)
Abstract: Introduction: One of the society’s health problems is prenatal domestic violence. Violence may directly and indirectly affect the pregnancy outcome. In recent years, many different studies have been conducted in Iran on the prevalence and consequences of prenatal domestic violence. However, no organized conclusions have yet been drawn from the results of these studies so far. This study aimed to examine the findings of the past decade of studies in Iran on the effects of prenatal domestic violence on maternal and fetal outcomes. Method: This study reviewed studies of the past decade in Iran that investigated the prevalence and consequences of prenatal domestic violence on maternal and fetal outcomes. These articles were searched by using available information in databases; Pubmed, Magiran SID, Iranmedex, and Irandoc from 2001 to 2011 using keywords [domestic violence, violence, spouse abuse, family violence, physical violence, sexual violence, and emotional violence] separately, and keywords [abusive behavior, pregnancy, pregnancy consequences, pregnancy outcome , pregnancy results, preterm labor, and low birth weight] collectively. Results: A total of 22 articles were reviewed, 16 of which were descriptive (sectional, longitudinal), and 6 were analytical (cohort and case/control). Out of the 22 studies, 14 had reported the prevalence of prenatal domestic violence and its types in different regions in Iran, 11 investigated the effects of domestic violence on fetal outcomes, and 11 investigated the effects of domestic violence and its types on maternal outcomes. Discussion and conclusion: Investigations revealed that, regardless of location and ethnicity, prenatal domestic violence is a common problem with important maternal and fetal consequences. These are common issues in obstetric medicine. Some of these outcomes are preventable both for the mother and for the fetus. It appears such incidences can be prevented by appropriate actions such as; life skill education and self-care, prenatal screening, increased prenatal care, presence of spouse in prenatal care sessions and important role of spouse during pregnancy. Thus, further studies focusing on identification of appropriate interventions to reduce and control these problems are recommended. Keywords: domestic violence, prevalence, abusive behavior, pregnancy, maternal outcome, pregnancy outcome